Long COVID and hypermobility spectrum disorders have shared pathophysiology - Ganesh, Ravindra; Munipalli, Bala (Frontiers in Neurology, 2024)
Hypermobility spectrum disorders (HSD) and hypermobile Ehlers–Danlos syndrome (hEDS) are the most common joint hypermobility conditions encountered by physicians, with hypermobile and classical EDS accounting for >90% of all cases. Hypermobility has been detected in up to 30–57% of patients with myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS), fibromyalgia, postural orthostatic tachycardia syndrome (POTS), and long COVID (LC) compared to the general population. Extrapulmonary symptoms, including musculoskeletal pain, dysautonomia disorders, cognitive disorders, and fatigue, are seen in both LC and HSD. Additionally, ME/CFS has overlapping symptoms with those seen in HSD. Mast cell activation and degranulation occurring in both LC and ME/CFS may result in hyperinflammation and damage to connective tissue in these patients, thereby inducing hypermobility. Persistent inflammation may result in the development or worsening of HSD. Hence, screening for hypermobility and other related conditions including fibromyalgia, POTS, ME/CFS, chronic pain conditions, joint pain, and myalgia is essential for individuals experiencing LC. Pharmacological treatments should be symptom-focused and geared to a patient’s presentation. Paced exercise, massage, yoga, and meditation may also provide benefits.